La evaluación asociada a los estilos de aprendizaje en la asignatura matemática en el primero de bachillerato general unificado - Mora Heras, Nicole Aracely (2022)
The purpose of this study is to determine the characteristics that the evaluation associated with visual and auditory learning styles should have, for the development of an evaluation proposal in Mathematic in the First year of the Unified General High School. It was developed with a methodology based on the qualitative approach, design and documentary review method. In order to synthesize the information, the checking technique was applied, the elaboration of logbooks and content cards. Among the results obtained, it was determined that the person learns visually with a higher percentage than auditory, therefore, both styles should be considered in the evaluation planning. The evaluation associated with visual and auditory learning styles is characterized by incorporating techniques such as observation, achievement, achievement analysis and questioning; It also instruments such as includes instruments such as rubrics, checklists and questionnaires; the strategies for visual learning are the use of pictures, colors, mind maps; and for auditory learning, the use of video, sound recordings, brainstorming, explanation to other classmates, among the most important ones. Keywords: Learnig styles, educational evaluation, visual learning, auditory learning.